Scientific Importance of Application of International Assessment Programs in the Integration of Education of Uzbekistan with World Education - Dilova Nargiza Gaybullaevna (Zien Journals, 2022)
The article deals with the problems of international assessment programs, their integration with world education when using them, the scientific novelty of using international assessment programs, the problems of improving the development of students' competence through training and test tasks based on the PIRLS international assessment program. tasks in education.
Keywords: international assessment programs; world education; integration; test tasks